Immunohistochemical expression of TRPS1 in mammary Paget disease, extramammary Paget disease, and their close histopathologic mimics. (1st March 2023) - Cho, Woo Cheal; Ding, Qingqing; Wang, Wei‐Lien; Nagarajan, Priyadharsini; Curry, Jonathan L.; Torres‐Cabala, Carlos A.; Ivan, Doina; Albarracin, Constance T.; Sahin, Aysegul; Prieto, Victor G.; Aung, Phyu P.
Abstract: Background: Trichorhinophalangeal syndrome type 1 (TPRS1) expression has been found to be highly sensitive and specific for breast carcinomas. The frequency of TRPS1 expression in cutaneous neoplasms such as mammary Paget disease (MPD) and extramammary PD (EMPD) is currently unknown. We assessed the utility of TRPS1 immunohistochemistry (IHC) in the evaluation of MPD, EMPD, and their histopathologic mimics, squamous cell carcinoma in situ (SCCIS) and melanoma in situ (MIS). Methods: Twenty‐four MPDs, 19 EMPDs, 13 SCCISs, and 9 MISs were subjected to immunohistochemical analysis using anti‐TRPS1 antibody. The intensity (none, 0; weak, 1 + ; moderate, 2 + ; strong, 3 + ) and proportion (<1%, absent; 1%–25%, focal; 26%–75%, patchy; >75%, diffuse) of TRPS1 expression were recorded. Relevant clinical data were documented. Results: TPRS1 expression was present in 100% (24/24) of MPDs, with 88% (21/24) of MPDs exhibiting strong, diffuse immunoreactivity. Sixty‐eight percent (13/19) of EMPDs showed TRPS1 expression. Intriguingly, EMPDs lacking TRPS1 expression were consistently of perianal origin. TRPS1 expression was seen in 92% (12/13) of SCCISs but was absent in all MISs. Conclusions: TRPS1 may be useful to distinguish MPDs/EMPDs from MISs, but its utility is limited in distinguishing them from other pagetoid intraepidermal neoplasms such as SCCISs.